Efficacy of ixekizumab in patients with moderate-to-severe plaque psoriasis and prediabetes or type 2 diabetes - Egeberg, Alexander; Merola, Joseph F.; Schäkel, Knut; Puig, Luis; Mahar, Patrick D.; Wang, Isabella Yali; Pavo, Imre; Schuster, Christopher; Griffiths, Christopher E. M. (Frontiers in Medicine, 2023)
Objective: Patients with psoriasis have an increased prevalence of type 2 diabetes when compared to the general population. 1 Research suggests that type 2 diabetes (T2D) as well as obesity may have an impact on patients’ response to treatment. This post-hoc analysis reports the efficacy of ixekizumab in treating moderate-to-severe psoriasis in patients with prediabetes or T2D. Method and Materials: UNCOVER-1, UNCOVER-2, and UNCOVER-3 were three Phase 3, multicenter, randomized, double-blind, placebo-controlled trials that evaluated the efficacy and safety of ixekizumab in adult patients with moderate-to-severe psoriasis. Patients were aged ≥18 years with chronic moderate-to-severe psoriasis (defined as ≥10% body surface area affected, static Physician Global Assessment ≥3, and Psoriasis Area and Severity Index [PASI] ≥12 at screening and baseline) who were candidates for phototherapy or systemic therapy. UNCOVER-1, UNCOVER-2, and UNCOVER-3 participants received ixekizumab as per label (that is, an initial dose of two subcutaneous injections [160mg in total] at Week 0, followed by 80mg every 2 weeks through Week 12 and 80mg every 4 weeks thereafter through Week 60). Results: The proportions of patients with prediabetes, T2D and normoglycemia that achieved PASI75, PASI90, and PASI100 at Week 60 were similar. Results suggest that patients with T2D were slower to achieve PASI100 than patients with prediabetes or those with normoglycemia. Ixekizumab had no effect on any metabolic markers in patients receiving the treatment. Conclusions: Despite the higher rate of obesity and extreme obesity in patients with prediabetes and T2D, ixekizumab was an efficacious treatment in treating patients with psoriasis.